A first principles study on H-atom interaction with bcc metals. (26th March 2023) - Fu, Yang; Li, Tong; Yan, Ya-Bin; Wang, Xiao-Yuan; Zhu, Ming-Liang; Xuan, Fu-Zhen
Abstract: Solute hydrogen trapping has long been proposed as one of the mechanisms for hydrogen embrittlement in steel. It has been reported that the maximum hydrogen trapping energy of metallic solutes ranged from −0.7 eV to −0.9 eV. In this work, the mechanism of metal-H interaction in Cr-Mo steels was investigated with first principles calculations by modelling the binary alloy Fe-X (X = C, Si, Mn, Cr, Mo) system with reference to the chemical composition of Cr-Mo steels. The formation of hydrogen bonds in the case of H atoms located at different sites in Fe-X crystals was analyzed. Results indicated that various atomic doping had different roles in hydrogen effect in the steel, with C, Si and Mo doping making the solid solution of hydrogen in Fe crystals easier, while Mn and Cr doping was rather more difficult. In Fe-Mn and Fe-Cr crystals, the repulsion between Fe lattices was insignificant when H atoms were located in tetrahedral sites, which considerably reduced the binding energy in the crystal. When H atoms were dissolved into the crystal, the interatomic bonding interactions in Fe-X crystals were weakened, resulting in higher charge density fluctuations. The current work extends the understanding of H-atom diffusion and migration in steel from the microscopic scale to the atomic and electronic scales, which underpins the physics for tailoring chemical elements of bcc metals towards higher resistance to hydrogen embrittlement. Graphical abstract: Image 1 Highlights: Metal-H interaction was investigated with first principles in Fe-X system. Various atomic doping had different roles in hydrogen effect in the steel. The binding energy in Fe-Cr and Fe-Mo crystals varied with H atom location. Hydrogen embrittlement was associated with lower repulsion between Fe lattices. H-atom diffusion and migration was interpreted at atomic and electronic scales.